Pharmacokinetics of ß-d-N4-Hydroxycytidine, the Parent Nucleoside of Prodrug Molnupiravir, in Nonplasma Compartments of Patients With Severe Acute Respiratory Syndrome Coronavirus 2 Infection. (10th March 2022) - FitzGerald, Richard; Dickinson, Laura; Else, Laura; Fletcher, Thomas; Hale, Colin; Amara, Alieu; Walker, Lauren; Penchala, Sujan Dilly; Lyon, Rebecca; Shaw, Victoria; Greenhalf, William; Bullock, Katie; et al.
Abstract: ß-d-N4-hydroxycytidine (NHC), the parent nucleoside of molnupiravir, a COVID-19 antiviral, was quantified at SARS-CoV-2 transmission sites in 12 patients enrolled in AGILE Candidate-Specific Trial-2. Saliva, nasal, and tear NHC concentrations were 3%, 21%, and 22% that of plasma. Saliva and nasal NHC were significantly correlated with plasma ( P  < .0001). Clinical Trials Registration . NCT04746183.